Organizational design as a strengthen strategy for calcalizas small company in Nobsa, Boyacá - Calixto, Mónica Bibiana González; Plazas, Viviana Marcela Hernández; Balaguera, Luz Mery Corredor (Universidad Pedagógica y Tecnológica de Colombia, 2013)
Calcalizas is a mining small company located in the municipality of Nobsa, Boycá, Colombia, established 16 years ago and it is engaged in the exploitation and marketing of limestone and its derivates. The small company has remained in the market, but factors such as a lack of organization and strategic direction, caused that its competitors took advantage of this small company. For this reason, the search of a suitable organization to better its conditions, which would allow it a higher level of competitiveness, we proposed an organizational design for Calcalizas small company. From a business diagnosis view, internal and external information in the mining and construction sectors at regional and national level was analysed, after the organizational structure was designed and functions processes and procedures manuals were systematized. Interviews, workshops and meeting with the owner and employees and some customers were done in order to get information and socialize it. As a result, the company was well organized involving workers, achieving changes at strategic level with a focus on customers and identifying other opportunities of improvement. In addition, the need to adapt organizational design was confirmed, according to the specific characteristics of the small company and its environment, as well as to make it consistent with the strategy proposed.